Annual Plan 1997-98 Volume-V Sector : Social Services Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
Early Childhood Care and Education is meant to promote assured access to every child for the fulfillment of all basic needs through the period of his growth and preparation for formal schooling. ECCE is expected to provide for a holistic development of the child i.e. his social, educational, health, physical, nutritional and psychological needs. Altogether ECCE scheme is meant to integrate health, nutrition, social and educational components, taking care to see that education does not become a formal teaching of 3'Rs and an anticipation of the learning that should take place at the primary stage, but is an enjoyable introduction to the joyfulness of socialisation and learning, carried out through play way techniques to get the child ready for schooling.
Andaman and Nicobar Administration, Planning Department